Answer:
First choice is the correct one
Explanation:
The given is:
[(x+5) / (x+2)] - [(x+1) / x(x+2)]
First, we will need to have a common denominator and then we will solve the subtraction normally. To get a common denominator, we will have to multiply both numerator and denominator of first term by x.
Therefore:
[(x+5) / (x+2)] - [(x+1) / x(x+2)] = [x(x+5) / x(x+2)] - [(x+1) / x(x+2)]
= [x(x+5)-(x+1)] / [x(x+2)]
= (x^2 + 5x - x - 1) / [x(x+2)]
= [(x^2 + 4x - 1)] / [x(x+2)]
Hope this helps :)
Two hundred and seventy three point two hundred and sixty one
Answer:
j=8
Step-by-step explanation:
22-14=8